TÓTH GUTTMAN EMESE - LAUDATIO - Olga LUKÁCS (Studia Universitatis Babeş-Bolyai. Musica, 2023)
Laudatio - Her conscientious work, love of family and humanity, living the values of the Christian faith, serene personality, professional knowledge, and deep humility will serve as a worthy example for the generations of teachers to follow.